KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA- TANGAN TERHADAP KETEPATAN SMASH ATLET BOLAVOLI UNIVERSITAS ISLAM INDRAGIRI - Dahrial Dahrial (Jurnal Olahraga Indragiri, 2017)
: Based on the writer’s observation, volleyball players at University Islamic of Indragiri often fail in doing smash in a match undergo which results to unsatisfyied results. The goal of this study is to explore 1) the contribution of leg muscle’s explosive power toward the smash accuracy, 2) the contribution of hand-eyes coordination toward the smash accuracy, 3) the contribution of leg muscle’s explosive power and hand-eyes coordination toward the smash accuracy in a volleyball game. This research belongs to a quantitative research. The object of the research is 32 male volleyball players of University Islamic Indragiri. The sampling method is used in the research is total sampling. The instruments of the study is vertical jump for leg muscle’s explosive power test, ballwerfen und fangen for hand-eyes coordination test, and smash accuracy assessment is analyzed using simple and double regression correlation. The result of this research showed that the explosive power of leg muscle contributes toward the smash accuracy of volleyball athlete at University Islamic of Indragiri up to 13,41%, the hand-eyes coordination contributes significant toward the smash accuracy of volleyball athlete at University Islamic of Indragiri up to 16,84%. Meanwhile, the result using techniques of correlation and multiple regression analysis revealed that the explosive power and hand-eyes coordination contributes significantly toward the smash accuracy of volleyball athlete at University Islamic of Indragiri up to 26,32%.